The value of public spaces for sustainable cities in the context of urbanization and urban development - Akyildiz, Öğretim Üyesi Nihal Arda (Milli Folklor Dergisi, 2020)
In modern life, the city is the whole of living spaces that can meet the social needs in a social, cultural and economic context while keeping people together with certain rules within a certain organization with many independent levels of life. Today's cities have become the center of platforms where environmental and social problems are discussed for the last 50 years. With the issues such as environmental pollution triggering climate change and consumption of natural resources, the search for solutions to the growing problems of cities with their inadequacies in demographic and spatial planning decisions increases its importance day by day. Therefore, in recent years, the city has become one of the prominent subjects in scientific studies due to its importance. Derived from the concept of city; the concept of urbanization, which includes the adaptation process and the effort to be included in the system, is one of the main arguments of the city and urban space. The phenomenon of urbanization included the quality of the adaptation process by becoming a concept about the emotions, thoughts and behaviors of individuals trying to live in the city completely from the physical definition of urbanization. Cities have been diversified with the migrants they receive, with the views and habits of different sociocultural individuals, their dissimilar life philosophies and various spatial planes that enable them to coexist with harmony and harmony in social life. The concept of 'sustainable city' has emerged as a new urban design model due to the increasing pressure on the rapidly growing city horizontally and vertically with the increasing population and technological developments. In cities designed with this perspective; both spatial sustainability, which minimizes negative impacts on nature and transfers natural resources to future generations, as well as many spatial planes that diversify the daily social life of the city's inhabitants and support social sustainability. Based on the conceptual development and transformation of the concept of the city, the study aims to reveal the contribution of the development or restructuring of ' public spaces', one of the important urban spaces supporting the spatial and social sustainability of urban development, to urban planning Public spaces have become a rapid and powerful momentum for urbanism and architecture with their social and spatial benefits as the areas of integration and interaction for the urban population in the rapidly increasing urban population. Public spaces that constitute the essence and centers of gravity of the city; are the elements that give identity to the city both historically and geographically. One of the main objectives of sustainable urban policies is to transform people from different parts of the city into an integrated structure together with public spaces, which is a meeting place where individuals from different socio-cultural and economic groups participate. This study predicts the value of the spatial plane in which public spaces, which are important planning tools of sustainable urban development, act as an important catalyst and will add to the urban social life as a center of interaction and integration. In the study, sustainable urban design public spaces; examining the city's history, culture, silhouette, local economic vitality, social interaction area as well as its contribution to the city is described and discussed. © 2020, Milli Folklor Dergisi. All rights reserved.
Kentleşme ve kentsel gelişim bağlaminda açik kamusal alanlarin sürdürülebilir kentler açisindan değeri
Keywords: City/urban; Public spaces; Sustainable urban development; Urban design; Urbanization